IMPLEMENTASI PROGRAM TAHFIZUL QUR’AN DALAM MEMBENTUK KARAKTER RELIGIUS SISWA DI SMA SWASTA BUDI AGUNG MEDAN - Reyhan Fahira Nasution; Khairuddin Khairuddin (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
In the current era of globalization, there is a lot of news about the decline in morals or religious character of adolescents who are students. But very few teenagers excel in studying and memorizing the Qur'an. Therefore, we should be able to change the religious character of Islamic students for the better, one of which is through the role of education. Every educational institution has a share to instill religious character in its students by planting the values contained in the Qur'an, such as making the Tahfizul Qur'an program. Therefore, this study aims to see the implementation of the Tahfizul Qur'an program at SMA Swasta Budi Agung Medan in shaping the religious character of its students. This research is field research, using a qualitative approach by collecting data through interviews, observation, and documentation. The Tahfizul Qur'an program is implemented 4 days a week with ziyadah activities (adding new memorization) and muraja'ah (repeating memorization). The method used to memorize is the method. Tasmi’ (listening and listening). But there are still many inhibiting factors in the implementation of the Qur'an Tahfizul program at SMA Swasta Budi Agung Medan, including 1. limited learning time allocation, 2. uncomfortable classroom facilities, 3. lack of educators who are experts in the field of Tahfiz, 4. inconsistent parental support in guiding children to memorize at home, the implementation of the Tahfizul Qur'an program in shaping the religious character of students at SMA Swasta Budi Agung Medan is exemplary, such as the way of dressing, speaking, behaving, polite, disciplined, active in worship, and having better religious knowledge.